Перформанс у хореографії як відображення соціальних смислів в Україні - Заєць Світлана; Zaiets Svitlana (Видавництво «Код», 2025)
Резюме. У статті зазначено історичний період виникнення перформативного мистецтва; розкрито сутність та особливості хореографічного перформансу. Розкрито змістове відображення соціальних смислів та проблем у хореографічних перформансах: інклюзії, екології, теми війни, геноциду, гендерної нерівності, психологічної напруги в суспільстві та індивідуальних переживань людини.

Abstract. The article identifies the historical period in which performative art emerged and outlines the essence of performative art, as well as the specific features of choreographic performance, where the creative process itself rather than the final result is of primary importance. It explores how social issues are reflected in choreographic performances, including themes of inclusion, ecology, war, genocide, gender inequality, psychological tension within society, and interpersonal dynamics. The publication mentions Ukrainian choreographers-performers such as Krystyna Shyshkaryova, Yaroslav Kainar, Oleksii Skliarenko, Iryna Mazur, Olha Kebas, and Larysa Venediktova. The article examines the current state of performative art created by Ukrainian choreographers and analyzes how social meanings and the problems facing Ukraine are expressed in choreographic performances. It provides an example of the work of an inclusive laboratory and offers a brief overview of DancePlatforma.ua a Ukrainian platform established to support the development of contemporary dance and choreography. The platform aims to unite dancers, choreographers, and instructors from various dance fields, offering opportunities for professional growth, knowledge exchange, and the presentation of works to a wide audience. The article highlights the project «Speak with the Body», which functions as a hub for Ukrainian contemporary dance during the war. The project provides Ukrainian choreographers and dancers who continue their work with an online platform to showcase and preserve their creations; disseminate collected materials and information about the Ukrainian dance community to national and international audiences; define key questions surrounding «contemporary dance art during wartime»; and encourage artists to remain active and seek new tools for embodied expression. The content of social meanings conveyed in choreographic performances and video works by Ukrainian dancers, artists, and performers is also examined.
Performance in choreography as a reflection of social meanings in Ukraine
Весь випуск: https://sites.google.com/uica.education/nayka/%D0%BD%D0%B0%D1%83%D0%BA%D0%BE%D0%B2%D1%96-%D0%B7%D0%B0%D0%BF%D0%B8%D1%81%D0%BA%D0%B8-17?authuser=0
Keywords: перформативне мистецтво; хореографічний перформанс; соціальні смисли; українські перформери; хореографічний проєкт